PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA PASAR MODAL. - Shobirin, Noval (E-Jurnal Akuntansi, 2012)
Disclosure of CSR becomes one of the ways the company to show a good performance to the public and investors. With the disclosure, the company will get the image and recognition of the good, that the company was also responsible for the environment surrounding the company. So the company will have appeal in capital investment. The capital market is one of the instruments for capital formation of companies, as well as from its own capital and capital of the debt. In addition to the corporate capital-forming, as capital markets become a quality indicator of the company through the company's share price. This research aims to analyze and provide empirical evidence of influence among the three dimensions of disclosure of corporate social responsibility (CSR-disclosure) based on the Global Reporting Initiative (economic, environmental, and social) of the performance of the capital market which is pro xy with the stock price. Analysis techniques were used to solve the problem in this research are multiple linear regression. Results of the study showed that the higher the Social Dimension of CSR disclosure improve capital market performance significantly. While the disclosure of the economic and environmental dimension of CSR to improve the performance of the capital market is not significant at the manufacturing companies listed in BEI in 2010-2011. Key Words : CSR disclosure, capital market , share price .